Maternal and perinatal outcomes of rupture uterus at rural tertiary care institution: a retrospective study - Singh, Mamta; Kanti, Vaibhav; Seth, Shikha; Gupta, Vandana; Kumari, Kalpna; Mishra, Pragati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Rupture of the pregnant uterus is a life threatening, preventable obstetric complication associated with high maternal and fetal mortality and morbidity. The objective of this study was to determine the incidence, maternal and perinatal outcome of rupture uterus at a rural tertiary care institution. Methods: Retrospective study included all uterine rupture cases booked or unbooked in hospital over a period of 6 years from January 2009-December 2014. In all patient’s case files, labour room and theatre records were reviewed and analyzed. Uterine rupture cases were categorized into complete and incomplete. Complete rupture was defined as full thickness uterine wall defect and incomplete rupture as small uterine wall defect. Only complete uterine rupture cases were included in the study. Cases with uterine dehiscence or other partial defects of uterine wall were excluded. Results: Total of 57 cases of uterine rupture was managed during the 6 years study period. In this period there were a total of 28,607 deliveries, giving a ratio of 1:502 and incidence of uterine rupture was calculated to be 0.199%. There were 43 (75.4%) rupture in scarred and 14 (24.56%) rupture in unscarred uterus. Majority (52.63%) were in age group 21-30 years, 42.10% cases were in age group 31-40 years. Maximum (91.2%) patient were between paraity 1 and parity 4, at 36-40 weeks of gestational age. 89.5% unbooked, 59.6% of rupture were managed with scar repair, 36.84% had bilateral tubal ligation done along with scar repair. 40.3% underwent hysterectomy (subtotal 29.82% and total abdominal hysterectomy 10.52%). Commonest complication was anemia for which multiple transfusions were given. In 5.3% bladder repair was done. Maternal mortality due to rupture was 8.77%. Perinatal mortality was 85.9%. Conclusions: Incidence of rupture is very high in our rural tertiary center. Mortality and complications due to rupture can be decreased by regular antenatal visits, early referral, taking timely and active interventions and blood transfusions.